Research on the application of microwave expanded fine-cut heavily rolled stems. Issue 6 (January 2021) - Zou, Quan; Feng, Hongtao; Zhang, Tao; Hu, Qun; He, Xufeng; Wu, Jiacan; Pu, Qian; Zhao, Meiwei; Qiu, Ye; Yang, Lei
Abstract: In order to improve the adaptability of slim cigarettes blended with cut stems. In this study, we have developed the microwave expanded fine-cut heavily rolled stems. By setting the different proportions of cut stems, compared with the traditional pneumatically dried cut stems, we analyzed the application characteristics of the microwave expanded fine-cut heavily rolled stems into the slim cigarette from the aspects of blending uniformity, physical characteristics of cigarette, mainstream smoke, sensory quality. The results showed that: the microwave expanded fine-cut heavily rolled stems is conducive to the Blending Uniformity, the draw resistance stability is better than that of the traditional pneumatically dried cut stems, the adaptability in slim tobacco is better than that of the traditional pneumatically dried cut stems, the stability of tar and CO release is improved, and the overall sensory quality of the microwave expanded fine-cut heavily rolled stems is better in sensory evaluation. This study supports the application of the microwave expanded fine-cut heavily rolled stems in the slim cigarettes.